Inteligencia Emocional en Estudiantes de la Facultad de Ingenieria de la Universidad Nacional de Chimborazo. Riobamba. marzo-julio 2017.” - Gusqui Cayo, Luis Henrry (2017)
The objective of this research was to describe emotional intelligence dimension development in students from Engineering College at the National University of Chimborazo in April-July 2017. This research details some students’ emotional problem characteristics, including the development and management of their own emotions. For the research development, a mixed paradigm was established, predominantly quantitative, with a non-experimental design, based on a descriptive level of research. 20 students between men and women were part of the sample. TMMS-24 psychometric test was used for data collection and obtain results. Three emotional intelligence dimensions were taken into account on this research such as emotional perception, emotional comprehension, and emotional regulation. The results of the research are based on a correlation of the components of emotional intelligence, which identifies that the male gender in terms of perception components and regulation have a higher level over women. They have the capacity to express the feelings in an appropriate way. Regarding the regulatory component, women are able to regulate their emotional states correctly instead. This research established that institutional educational system is related to emotional intelligence in a significant way.